Comparative Analysis of Amino Acid Profile of Tenualosa Ilisha and Catla Catla and Their Potential Contribution to Recommended Nutrient Intake (Bioresearch Communications, 2023)
Objective: The current study aimed to determine the amino acid profiles and proximate compositions of two commonly consumed fish species of Bangladesh: Tenualosa ilisha and Catla catla, commonly known as Hilsha, the national fish of Bangladesh and Catla, respectively.Methodology: The fish samples were collected from two wholesale fish markets (ghaats) in Dhaka city, the capital of Bangladesh. The Amino Acid content of the selected samples was analyzed by an amino acid analyzer. Fourteen amino acids (eight essential and six non-essential) could be detected by the analyzer.Results: In the case of the essential amino acid content of the samples, threonine, valine, isoleucine, histidine, and lysine content was greater in the Hilsha fish than that of Catla. On the other hand, methionine, leucine, and phenylalanine content were higher in Catla than that in Hilsha. All six non-essential amino acids were found in greater amounts in Hilsha. Concerning the potential contribution (%) of the selected samples to the daily recommended nutrient intake (RNI) of essential amino acids in children (5-10 years), Hilsha fish potentially contributes (>50%) to the daily RNI of threonine, methionine, and lysine and Catla fish potentially contributes (>50%) to the daily RNI of methionine and lysine. In regards to the adult’s RNI, Hilsha potentially contributes (>50%) to the daily RNI of methionine and lysine but Catla was found to contribute potentially (>50%) to the daily RNI of methionine only.Conclusion: Both of the samples were found to be a substantial source of protein and essential amino acids to significantly contribute to the daily RNI of essential amino acids concerning children (5-10 years) for growth and adults for maintenance.Bioresearch Commu. 10(1): 1371-1377, 2024 (January)